BDNF Modulation of NMDA Receptors Is Activity Dependent - Crozier, Robert A. (American Physiological Society, 2008)
Brain-derived neurotrophic factor (BDNF), a potent modulator of synaptic transmission, is known to influence associative synaptic plasticity and refinement of neural connectivity. We now show that BDNF modulation of glutamate currents in hippocampal neurons exhibits the additional property of use dependence, a postsynaptic mechanism resulting in selective modulation of active channels. We demonstrate selectivity by varying the repetition rate of iontophoretically applied glutamate pulses during BDNF exposure. During relatively high-frequency glutamate pulses (0.1 Hz), BDNF application elicited a doubling of the glutamate current. During low-frequency pulses (0.0033 Hz), however, BDNF evoked a dramatically diminished response. This effect was apparently mediated by calcium because manipulations that prevented elevation of intracellular calcium largely eliminated the action of BDNF on glutamate currents. To confirm N-methyl-d-aspartate (NMDA) receptor involvement and assess spatial requirements, we made cell-attached single-channel recordings from somatic NMDA receptors. Inclusion of calcium in the pipette was sufficient to produce enhancement of channel activity by BDNF. Substitution of EGTA for calcium prevented BDNF effects. We conclude that BDNF modulation of postsynaptic NMDA receptors requires concurrent neuronal activity potentially conferring synaptic specificity on the neurotrophin's actions.